Long-term effects of the 11+ warm-up injury prevention programme on physical performance in adolescent male football players: a cluster-randomised controlled trial - Zarei, M.; Abbasi, H.; Daneshjoo, Barghi, T. S.; Rommers, N.; Faude, O.; Rössler, R. (Journal of Sports Sciences, 2018)
This study examined the long-term effects of the 11+ on physical performance in adolescent male football (soccer) players. Eighty-two 14- to 16-year-old male football players (11+ = 42 players, control = 40 players) participated. Teams were randomised to control (CON) and intervention (INT) groups. INT applied the 11+ injury prevention programme for 30 weeks at least twice a week as a warm-up. CON performed their standard warm-up. Motor performance tests were conducted 1 week prior and 1 week after the competition season. We used magnitude-based inferences and linear mixed-effects models to analyse performance test results. INT showed superior results compared to CON in the vertical jump height 7.5% (95%-CI 4.4%, 10.7%), the Bosco 15-s-jump test 7.2% (95%-CI 2.2%, 12.4%), and the Illinois agility test -2.6% (95%-CI -4.1%, -1.1%). Possibly beneficial effects in favour of INT were found in the 9.1 m sprint test -3.1% (95%-CI -6.1%, 0.1%). Possibly harmful effects (i.e. in favour of CON) were observed in the dribbling test 2.8% (95%-CI -0.8%, 6.4%). The 11+ warm-up programme can improve different performance measures in football players. Coaches might implement additional dribbling drills next to the 11+ to achieve improvements observed in dribbling ability when using a regular warm-up programme.